Do marketing strategies have significant influence on usage of credit cards? empirical evidence from Malaysia - Kassim, Salina; Hussin, Siti Rahayu (UPM Press, 2016)
This study explores the impact of marketing strategies of credit card providers on credit card users in Malaysia. It investigates customers’ perception of credit card products, promotions, pricing and place strategies. Credit card usage patterns are observed in terms of card possession, usage frequency, spending amount and usage motivation. The study adopts a quantitative research approach through survey questionnaires to link marketing strategies with credit card usage. Logistic regression was performed to determine the relationship between marketing strategies and credit card usage. The 4Ps of credit card providers’ marketing strategies (namely product, pricing, promotion and place/availability)have been shown to exert various degrees of influence on credit card usage. The study found product, pricing and availability strategies influence credit card usage, but there is no significant relationship between promotion strategies and credit card usage among Malaysians.